New bio-based polymeric thermosets synthesized by ring-opening polymerization of epoxidized soybean oil with a green curing agent. (November 2016) - Chen, Yahua; Xi, Zhenhao; Zhao, Ling
Graphical abstract: Highlights: Epoxidized soybean oil can be a good bio-based monomer for polymer synthesis. Method to synthesize a green curing agent, maleopimaric acid, was optimized. Bio-based thermosets were obtained from epoxidized soybean oil and maleopimaric acid. Novel thermosets exhibited long breaking elongations and great thermal stabilities. Novel thermosets shows potential to replace petroleum-based ones in some fields. Abstract: New polymeric thermosets with a high bio-based content were obtained by the ring-opening polymerization of two biomass derivatives, epoxidized soybean oil and maleopimaric acid, catalysed by 2-ethyl-4-methylimidazole. Maleopimaric acid with a rigid hydrogenated phenanthrene ring structure was successfully synthesized in a large quantity from abietic acid and maleic anhydride using p -toluene sulfonic acid as a catalyst, by adapting and optimizing an industrial strategy. The advantages of using maleopimaric acid as a curing agent for epoxidized soybean oil, compared with its petroleum-based analogues, were studied in detail. The results showed that the total heat release for the ring-opening polymerization of epoxidized soybean oil and maleopimaric acid was only 31.7 kJ/mol epoxy group. The tensile properties and glass transition temperature of the thermosets cured by maleopimaric acid were close to those of the products cured by the analogue with a cycloaliphatic ring, while the breaking elongation and storage modulus at room temperature of the former were greatly larger, exhibiting values of 61.5% and 1268 MPa, respectively. Additionally, the products cured with maleopimaric acid had the best thermal stability with a 10%-weight-loss temperature up to 349 °C and satisfactory chemical and water resistance.